A randomized trial to assess the immediate impact of acupuncture on quantitative sensory testing, pain, and functional status. Issue 11 (November 2019) - Chen, Lucy; Deng, Hao; Houle, Timothy; Zhang, Yi; Ahmed, Shihab; Zhang, Vivian; Sullivan, Shelly; Opalaze, Arissa; Roth, Sarah; Falacova, Jen; St Clair, Kristan; Vo, Tran; et al.
Abstract : Abstract: In this randomized clinical trial, we examined whether the effect of true acupuncture can be differentiated from sham acupuncture (pain and functionality) by analyzing quantitative sensory testing (QST) profiles in chronic pain participants. We recruited 254 healthy or chronic back and neck pain participants. Healthy subjects were included to control for a possible effect of acupuncture on baseline QST changes. Study participants received 6 sessions (twice weekly) of true acupuncture, sham acupuncture, or no acupuncture treatment (routine care). Quantitative sensory testing profiles, pain scores, and functionality profile were obtained at baseline (visit 1) and after 3 (visit 4) or 6 sessions (visit 7). A total of 204 participants were analyzed. We found no QST profile changes among 3 groups ( P = 0.533 and P = 0.549, likelihood ratio tests) in either healthy or chronic pain participants. In chronic back and neck pain participants, true acupuncture reduced pain (visit 4: difference in mean [DIM] = −0.8, 95% confidence interval [CI]: −1.4 to −0.1, adjusted P = 0.168; visit 7: DIM = −1.0, 95% CI: −1.7 to −0.3, adjusted P = 0.021) and improved functional status including physical functioning (DIM = 14.21, 95% CI: 5.84-22.58, adjusted P = 0.003) and energy/fatigue (DIM = 12.28, 95% CI: 3.46-21.11, adjusted P = 0.021) as compared to routine care. Our results indicate that QST was not helpful to differentiate between true acupuncture and sham acupuncture (primary outcome) in this study, although true acupuncture reduced pain and improved functionality (secondary outcomes) when compared with routine care. Abstract : Supplemental Digital Content is Available in the Text.This study shows that using quantitative sensory testing alone does not help differentiate the outcome between true acupuncture and sham acupuncture.